Calder Brand [large type] - Dailey, Janet (Dailey, Janet. Calder Brand, 2021)
A first installment in a Calder series spin-off is set in the late 1800s and follows the experiences of a vengeful cowboy and an aspiring doctor whose respective ambitions are complicated by past demons and an illegitimate child.